2012
DOI: 10.1002/jbm.b.32841
|View full text |Cite
|
Sign up to set email alerts
|

Development of sustained‐release antibacterial urinary biomaterials through using an antimicrobial as an organic modifier in polyurethane nanocomposites

Abstract: Urinary catheters are among the most frequently used medical devices in clinical practice. However, their use is associated with high rates of nosocomial infection. This study investigates the use of polyurethane nanocomposites (PUNCs) incorporating an antimicrobial agent, chlorhexidine diacetate (CHX), behaving as nanoparticle dispersant and model drug/active agent, as sustained-release antibacterial biomaterials in urinary devices. A range of PUNCs incorporating organically modified silicate (OMS) nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The FTIR spectra show the characteristic vibrational bands of CHX at 1665 cm -1 corresponding to the C=N-H stretching vibration [27], as well as the absorption bands corresponding to the aromatic C=C stretching located at 1537 and 1490 cm -1 [12]. In this way, the presence of the CHX in the membranes after processing was confirmed [28]. …”
Section: Fourier Transformed Infrared Spectroscopymentioning
confidence: 90%
“…The FTIR spectra show the characteristic vibrational bands of CHX at 1665 cm -1 corresponding to the C=N-H stretching vibration [27], as well as the absorption bands corresponding to the aromatic C=C stretching located at 1537 and 1490 cm -1 [12]. In this way, the presence of the CHX in the membranes after processing was confirmed [28]. …”
Section: Fourier Transformed Infrared Spectroscopymentioning
confidence: 90%
“…2 Single inorganic and polymer biomaterials are difficult to meet all the requirements, due to various disadvantages. [5][6][7] BGs have excellent biodegradability, biocompatibility and osteoconductivity, while BG has the ability to form a chemical bonding in contact with living tissue through a bonelike apatite mineral phase. 3,4 Among nanocomposite biomaterials, bioactive glass (BG)based polymer composites have been paid a lot attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared materials were first examined to assess surface expression of the two modifiers. While it has previously been shown that OMs used to modify silicate layers migrated out of the polymer matrix, altering biological interactions, 15,19 it was hypothesised in this study that OMs were being surface expressed. ToF-SIMS analysis of the two OMSs before incorporation in PEU showed peaks present at 186 and 216 (data not shown).…”
Section: Surface Analysismentioning
confidence: 88%
“…Although evidence of 12COOH was not detected on the surface of the PUNCs, we have previously shown migration and release of this OM from the NC system. 15,19 This apparent contradiction can be rationalised by surface energy considerations: when the PU surface is in contact with air, molecules more hydrophobic than the PU are energetically favoured to accumulate at the interface, whereas for hydrophilic molecules, it is energetically unfavourable to be located at the PU/air interface. Thus, methyl terminated OM molecules, which are hydrophobic, can be expected to migrate to the PU/air surface, whereas the hydrophilic COOH terminated OM molecules experience no such driving force, and thus, it is energetically more favourable for them to remain associated with the silicate nanoparticles.…”
Section: Surface Analysismentioning
confidence: 95%
See 1 more Smart Citation